Analysis of Water Quality Status Based on Domestic Waste Parameters by Using Pollutant Index Method at Tabuk River, Central Kalimantan Province - Nora Forina; Emmy Sri Mahreda; Mijani Rahman; Mahmud Mahmud (Postgraduate Program - Lambung Mangkurat University (ULM Press Academic), 2018)
The study aims to analyze the quality of water at Tabuk River Status by using pollution index method and domestic waste pollution impact to human health. The experiment was conducted in Tabuk River at Barito Selatan Regency Central Kalimantan Province. The samples of water with physical, chemical and biological parameters were taken at 3 points in the morning in the withdraw and flood. After wards, they were compared with the standard quality of water class II based on Government Regulation Number 82 of 2001 and domestic waste pollution impact to human health description. The results of study revealed that the water quality of Tabuk River exceeding criteria based on BOD at 48 mg/L in the withdraw and 22,52 mg/L in the flood, COD at 61,4 mg/L in the withdraw and 47,47 mg/L in the flood, TSS at 338,3 mg/L in the withdraw and 157,4 mg/L in the flood and Faecal Coliform at ≥ 1898 MPN. Whereas based on the index value of pollutants, Tabuk River by the light polluted status of 3,33-3,97, except downstream of withdrawing is medium (pollution index 5,2). The domestic waste pollution negative impact to human health. Increased faecal coliform in Tabuk River at ≥1898 jml/100 mL (MPN) and 58,33% society coastal river area have diarrhea and itch.